P705 Dietary practices and beliefs of patients with older-onset inflammatory bowel disease: A prospective UK study. (15th January 2020) - Crooks, B; McLaughlin, J; Limdi, J K
Abstract: Background: In an aging population, 25–35% of those with inflammatory bowel disease (IBD) are over 60 years old. A third of these are diagnosed at or over the age of 60 (older-onset IBD). Virtually no studies exist exploring the dietary practices and beliefs of patients with older-onset IBD. Elderly patients with IBD are at increased risk of nutritional deficiency and associated complications making it all the more important to understand the dietary habits and self-imposed restrictions of this group. Methods: A prospective, cross-sectional, questionnaire-based study is being conducted across NHS Trusts within the UK. Two-hundred patients with older-onset IBD will be recruited to complete a questionnaire regarding demographics and dietary practices. Here we provide an interim analysis of the data collected from the first 75 patients. Results: Mean patient age is 73 years, 51% are male and 95% Caucasian. 68% have ulcerative colitis. Mean disease duration is 6 years. Thirty-six per cent of patients believe diet was an initiating factor in their IBD and this is based on their own experience (78%) or advice from a gastroenterologist (33%), dietitian (22%) or GP (22%). Fifty-six per cent of patients report a disease relapse in the last year and just under a third believe that diet could trigger a relapse. The most commonly identified triggers are spicy foods (61%), raw fruit and vegetables (57%), fatty foods (39%) and milk products (30%). Sixty-three per cent of patients avoid certain foods to prevent a relapse of IBD. The most commonly avoided foods are spicy (81%) and fatty foods (66%), carbonated drinks (60%), red meat (53%), raw fruit and vegetables (49%) and alcohol (49%). Half of patients report being able to find specific advice regarding dietary recommendations in IBD and 72% of these obtain this information from the internet. A quarter of patients avoid eating the same menu as their family at least some of the time to prevent relapse of their IBD and 36% of patients avoid eating out. One in five patients has tried a specific exclusionary diet to help manage their symptoms, most commonly a gluten free diet, in the absence of coeliac disease, in 12% of patients. Conclusion: Despite a relatively low proportion of older-onset IBD patients believing diet is implicated in the initiation of their disease or its relapse, a significant number continue to restrict their diet. This, along with co-existing frailty, comorbidities and polypharmacy, may put this group of patients at increased risk of nutritional deficiency and its associated complications as well as impacting upon quality of life. Improved knowledge of the dietary habits of those with 'older-onset' IBD will allow healthcare professionals to identify those at risk and offer appropriate dietary interventions.